How to Thrive in Associate Staff Ministry - Lawson, Kevin E. (Rowman & Littlefield Publishers, 2000)
Contents include: Foreword, by Lovett H. Weems, Jr. Preface Introduction CHAPTER 1. Finding Satisfaction in Following God's Direction CHAPTER2. Working Well with Your Supervisor and Fellow Associates CHAPTER 3. Foundational Attitudes and Commitments CHAPTER4. Church Environments that Enable Thriving CHAPTER 5. Sustaining Personal Spiritual Vitality CHAPTER 6. Building Supportive Relationships CHAPTER 7. Strengthening the Home Front CHAPTER 8. Savoring Joys and Weathering Storms CHAPTER 9. Thriving Skills for Female Associate Staff CHAPTER 10. Veterans' Advice to "Wanna-bes" and "Newbies" Introduction to Appendixes A and B - For Those Who Care about Associate Staff APPENDIX A. The Valued Supervisor APPENDIX B. The Supportive Church Board APPENDIX C. The "Thriving in Associate Staff Ministry" Study APPENDIX D. Professional Organizations for Associate Staff Members Further Reading for Associate Staff Members